THE RELATIONSHIP BETWEEN SINGLE NUCLEOTIDE POLYMORPHISM OF INTERLEUKIN -10 GENE PROMOTER (-1082 A/G) WITH INFECTION CHLAMYDIA TRACHOMATIS INFERTILE IRAQI WOMEN. - & et al., Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Aim of  this studty  to identify the risk  of single nucleotide polymorphisms (SNPs) of IL-10 promoter variants -1082A/G  associated with Chlamydia trachomatis and tubal factor infertility.  Out of 100  women were attending different hospitals in Baghdad  included the Gynaecology Departments of Women Health Center at Al-Elwyia Obstetrics Hospital, Ibn Al balady Maternity and Children's Hospital , Kamal al-Samarrai hospital Fertility Center infertility treatment and In Vitro Fertilization ( IVF )  (20 control and 80 women with infertility) with an age range of 16-40 years. DNA was extracted from the endocervical  swabs of all infertili women, to investigate the bacteria using Real time -PCR technique and venous blood sample (2 ml) was obtained for DNA detection of IL-10Single Nucleotide Polymorphisms. The results revealed  the Diagnosis of  Chlamydia trachomatis by  Real time-PCR was significant responsible with infection in  infertile Iraqi women. (OR= 0.733; 13.75%,  P= 0.041). Among 80 infertilie women and patients women with  infertility diagnosis of Chlamydia  trachomatis  were  examined IL-10(-1082) promoter gene polymorphisms  were not found to be associated with  Chlamydia infections, indicating that this gene may not be involved in Chlamydia pathogenesis in Iraqi infertile women But in this study  the two new  mutation  showed (SNP -1218,-1213) was  detected in the promoter  region of the Interleukin-10 gene in infertile Iraqi women (AAT…..ATT),(GGC….GAC) mutations in  11 women with Infertilty associated with Chlamydia trachomatis infection